(untitled) (Research, Society and Development, 2021)
This work aimed to evaluate the influence of the addition of yam flour (Disocorea ssp.) on the color of fresh pasta, as well as its effects on their quality, in addition to proposing a greater added value to the yam, aiming to reduce its loss in Brazilian agribusiness, enabling greater possibilities of use for this tuber and promoting family farming. Four formulations of fresh wholegrain pasta were produced: control pasta (M0), containing 51% whole grain wheat flour (FIT) and 49% refined wheat flour (FRT), and in the other pasta, FB was replaced by flour at levels of 5, 10 and 15% (M1, M2 and M3, respectively). The percentage increase in substitution for yam flour (FI) resulted in lower dough moisture, with M3 being the one that differed statistically from the control dough. Regarding the firmness of raw pasta, the increase in HR increased the hardness of whole pasta, decreased the yield and increased the loss of solids during cooking. M2 was the one that presented quality parameters closest to M0 and was selected to evaluate the antioxidant capacity comparatively with M0. M2 showed higher values of ABTS and DPPH in relation to M0, and they did not differ in the total phenolic content (0.28 µg gallic acid equivalent / mg of dry sample). Yam flour showed a promising potential for use in whole pasta, both technological and functional, which can be beneficial to increase the added value of this tuber.